Causal effects of autoimmune diseases on temporomandibular disorders and the mediating pathways: a Mendelian randomization study - Chen, Xin; Cheng, Zheng; Xu, Junyu; Wang, Qianyi; Zhao, Zhibai; Jiang, Qianglin (Frontiers in Immunology, 2024)
Background: The role of autoimmune diseases (ADs) in temporomandibular disorders (TMDs) has been emphasized in observational studies. However, whether the causation exists is unclear, and controversy remains about which specific disorder is destructive in TMDs. This Mendelian randomization (MR) study aims to estimate the causal effect of common ADs on TMDs. Methods: Genetic data from published genome-wide association studies for fourteen common ADs, specifically multiple sclerosis (MS, N=15,283), ankylosing spondylitis (AS, N=22,647), asthma (N=408,422), celiac disease (N=15,283), Graves' disease (N=458,620), Hashimoto thyroiditis (N=395,640), primary biliary cirrhosis (PBC, N=11,375), primary sclerosing cholangitis (PSC, N=14,890), psoriasis vulgaris (N=483,174), rheumatoid arthritis (RA, N=417,256), systemic lupus erythematosus (SLE, N=23,210), Type 1 diabetes (T1D, N=520,580), inflammatory bowel disease (IBD, N=34,652), and Sjogren's syndrome (SS, N=407,746) were collected. Additionally, the latest summary-level data for TMDs (N=228,812) were extracted from the FinnGen database. The overall effects of each immune traits were assessed via inversevariance weighted (IVW), weighted median, and MR-Egger methods, and performed extensive sensitivity analyses. Finally, 731 immune cell phenotypes (N=3,757) were analyzed for their mediating role in the significant causality.Results: Univariable MR analyses revealed that genetically predicted RA (IVW OR:1.12, 95% CI: 1.05-1.19, p < 0.001) and MS (IVW OR: 1.06, 95% CI: 1.03-1.10, p = 0.001) were associated with increased risk of TMDs. Two out of 731 immune cell phenotypes were identified as causal mediators in the associations of RA with TMDs, including "CD25++ CD8+ T cell % CD8+ T cell" (mediation proportion: 6.2%) and "CD3 on activated CD4 regulatory T cell" (5.4%). Additionally, "CD127 on granulocyte" mediated 10.6% of the total effect of MS on TMDs. No reverse directions, heterogeneity, and pleiotropy were detected in the analyses (p > 0.05).Conclusions: This MR study provides new evidence regarding the causal impact of genetic predisposition to RA or MS on the increased risk of TMDs, potentially mediated by the modulation of immune cells. These findings highlight the importance for clinicians to pay more attention to patients with RA or MS when consulting for temporomandibular discomfort. The mediating role of specific immune cells is proposed but needs further investigation.